THE REVITALIZATION OF THE POSTAL MUSEUM THROUGH INTERACTIVE DISPLAY MEDIA AND EDUCATIONAL ZONES - Muhammad Khalil Gibran; Didit Widiatmoko Suwardikun; Hanif Azhar; Yanuar Rahman; Andreas Rio Adriyanto (Adisam Publisher, 2025)
This study explores the revitalization strategy of the Museum Pos Indonesia through the implementation of interactive display media and the arrangement of display zones based on visitor experience. The focus is directed toward transforming the previously conventional presentation of collections and exhibition spaces into formats that are more communicative, educational, and aligned with the needs of the digital generation. The research adopts a qualitative approach using Design Thinking (empathize, define, ideate, prototype, and test), supported by the Double Diamond framework from the UK Design Council. Data collection was conducted through observation, interviews, questionnaires, and literature review on the digitalization of educational spaces and user-centered design. The results indicate that technologies such as touchscreen displays, QR codes, and augmented reality (AR) can enhance visitor engagement and enrich the delivery of historical narratives. The reorganization of structured display zones also contributes to creating a more immersive and guided visitor experience. This study recommends the adoption of adaptive display systems that align with technological advancements and audience preferences, so that Museum Pos Indonesia may function not only as an archive but also as a dynamic and inclusive medium of cultural communication.